Legal Certainty on PPAT Authority in Making Deed Outside of His Location - Prakoso, Bhim; Suarda, I Gede Widhiana; Wardana, Dendik Surya (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This study aims to examine the legal certainty of the PPAT's authority in making deeds outside the area of his domicile. PPAT in carrying out its functions and authorities is limited by the working area, as regulated in PP PPAT in Article 12 paragraph (1) that the PPAT working area is "one working area of the Regency/Municipal Land Office". But then it was changed to one province area.” Based on the article, it is clear that the PPAT's work area has expanded, which was originally in the district/municipality area, now it is in the province. Legal issues studied 1). What is the basis for the amendment to Article 12 paragraph 1 of PP Number 24 of 2016 regarding the PPAT work area? 2). How is the legal certainty of the authority of the PPAT who makes the deed outside the domicile? The results of the study indicate that the expansion of the PPAT working area arrangement into one province as stipulated in Article 12 (1) PP No. 24 of 2016 caused problems due to the absence of implementing regulations. And when there is legal certainty about the authority of PPAT after the issuance of PP 24/2016, there is no implementing regulation in this case a Ministerial Regulation which is expected to be a guideline for PPAT in carrying out its authority. Suggestions in this study are for the government to review PP No. 24 of 2016 with the aim of maximizing the implementation of the rules by PPAT officials.